DESIGN OF A CASSAVAPROCESSING UNIT IN STARCH - NGNASSI DJAMI ASLAIN BRISCO; DOKA YAMIGNO SERGE; NZIE WOLFGANG (International Journal of Innovations in Engineering Research and Technology, 2021)
cameroonproducesmore than 2.5 million tonnes of cassava a year and nearly half of this production is consumed by local people as a subsistence crop. The activities of semi-industrial or industrial processing of cassava are almost non-existent because of the technological deficit. Hence the need to value local cassava production through the design of reliable and affordable machinery and processing units for farmers or peasant groups. The goal of this work is to design a cassava processing unit for starch. To do this, all our work was conducted at the Department of Mechanical Engineering of ENSAI. We worked on the design of the machines or compartments that were considered more critical for our unit, namely the cassava grater and the separator. The functional analysis approach, through the application of its various tools, made it possible to define the different modules of the machines that were designed. The bibliographic review associated with a field survey and interview allowed the selection of the grating and the separator which served as a basic prototype for the design process of an improved ripper and drum separator.